PERAN TOKOH MASYARAKAT DALAM PENANAMAN NILAI TOLERANSI PADA ETNIK MELAYU DAN TIONGHOA DESA NUSAPATI - Sulaiman, Sulaiman; Budjang, Gusti; Salim, Izhar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe title of this thesis is "The Role of Community Leaders in Planting Tolerance Values in Malay and Chinese Ethnics in Hamlet II, Nusapati River, Pinyuh River". The general problem in this research is "What is the shape of the role of community leaders in the establishment of tolerance values in Malay ethnic and Chinese hamlets IIDesa Nusapati, Pinyuh river". With sub-problems as follows; How to Form the Role of Community Leaders in Planting Tolerance Values in Mutual Respect; What Is the Shape of the Role of Community Leaders in Planting Tolerance Values of Mutual Concern in Malay and Chinese Ethnicities in Hamlet II, Nusapati Village, Pinyuh River. This study uses qualitative methods in descriptive form. The data collection tool uses interview guides and documentation. The results of the study show; Form of Role of Community Leaders in Planting Mutual Tolerance Values in the form of Community Leaders always appeal to the community to always live in harmony, must stay in touch with each other, give an example of behaving like always polite to their community whether they are young or old, and treat all people equally without looking at Ethnics, and giving reprimand such as giving advice or input to open the minds of the people to always behave well in maintaining harmonious life in the village; The Form of the Role of Community Leaders in Planting Mutual Concern Tolerance Values in the form of People here always teach to help and respect one another, by inviting the community to participate in activities to clean up the Village environment together, inviting people here to help other communities when they get disaster or again experiencing hardship, by inviting the community to make a contribution, teach or give an example to respect each other's community, for example not saying harshly to the people, always accepting or appreciating the opinions of their citizens regardless of ethnic or ethnic origin.        Keywords: Character Roles, Tolerance Values, Ethnicity.